Sintesis dan Uji Kinerja Membran Selulosa Termodifikasi Polistirena dari Ampas Tebu dengan Aditif Monosodium Glutamate untuk Menurunkan Nilai BOD dan COD Limbah Cair Tahu: Synthesis and Performance Testing of Modified Cellulose Membrane with Polystyrene Derived from Sugarcane Bagasse and Monosodium Glutamate Additive for Decreasing BOD and COD Values in Tofu Wastewater - Alvino Jefferson Sianipar; Senny Widyaningsih; Suyata (KOVALEN: Jurnal Riset Kimia, 2023)
Tofu liquid waste, which has high BOD and COD values, can contaminate waters if it is directly disposed of without prior treatment. Therefore, waste treatment is necessary before being released into water. One method for treating this waste is by using a cellulose acetate membrane. In this research, a cellulose acetate membrane was synthesized from sugarcane bagasse fibers using the phase inversion method. The membrane was added 6% MSG as an additive to improve its performance. The membrane was applied to treat tofu waste with BOD and COD parameters. The membrane’s flux values obtained in this study were 33.56 L/(m².hour) for water and 26.85 L/(m².hour) for tofu liquid waste. SEM test result showed that the membrane with a 6% MSG additive had more pores and a denser surface compared to the membrane without the additive. The membrane was capable of decreasing BOD and COD values by 62.5% and 75.3% respectively in liquid tofu waste.